Workforce Planning for the Future of Sports Tourism - Ronaghi, Seyedeh Sheida; Hosseini Semnani, Akram Sadat; Saffari, Leila (International Journal of Sport Studies for Health, 2024)
Objective: This review aims to provide a comprehensive analysis of workforce planning for the future of sports tourism, focusing on the current state, emerging trends, key skills and competencies, strategic workforce planning models, technological innovations, and policy implications. Methods and Materials: The review employs a descriptive analysis method, systematically gathering and synthesizing existing literature from peer-reviewed journal articles, industry reports, case studies, and government publications. Key databases and sources include Scopus, Web of Science, PubMed, and Google Scholar. Literature selection criteria included relevance to sports tourism and workforce planning, publication within the last 15 years, and availability in English. Findings: The study identifies significant contributions of sports tourism to global economies and highlights the necessity of strategic workforce planning to support industry growth. Emerging trends such as technological advancements, sustainability, and demographic shifts require new skills and competencies. Effective workforce planning models, including demand forecasting, competency-based planning, scenario planning, and talent management, are crucial for addressing future needs. Challenges such as funding constraints, skill gaps, and sustainability issues were identified, with recommendations for overcoming these barriers through targeted strategies and interdisciplinary approaches. Conclusion: Effective workforce planning is essential for the sustainable growth of sports tourism. Embracing technological innovations, promoting sustainability, and addressing cultural competence and diversity will be key to developing a skilled and adaptable workforce. Policymakers, industry leaders, and educators must collaborate to create supportive frameworks and training programs that align with future industry demands.